Nikah dengan Dua Akad dan Dua Wali yang Berbeda Perspektif Maslahah di KUA Wonokromo Surabaya - Hanif Nur Pradani (AL-HUKAMA, 2019)
This paper discusses the implementation of marriage with two different contracts and trustees at the Office of Religious Affairs (KUA) in Wonokromo, Surabaya. The data in this article is collected by documentation and interview with the head of KUA of Wonokromo and witnesses to marriage and analyzed using descriptive analysis technique. In the case of this marriage, the first marriage contract uses a nasab guardian because the marriage officer (penghulu) knows his nasab guardian is Muslim. Then the second contract uses the judge guardian because in the bride’s family card, the guardian is Christian. Even though it has been married by a nasab guardian, the head of KUA of Wonokromo listed in the marriage certificate is the judge guardian that the supporting documents in the marriage require the use of a judge’s guardian. This implementation is included in the maslahah mulghah because the use of the contract with the judge guardian is rejected by the proposition that he knew that the nasab guardian was Muslim. This means that if there is a legal guardian who has the right to marry, then the judge guardian does not need to be used.